Case reportInflammatory linear verrucous epidermal nevus – case report - Misterska, Małgorzata; Szulczyńska-Gabor, Joanna; Wolnik-Trzeciak, Grażyna; Walkowiak, Hanna; Żaba, Ryszard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Inflammatory linear verrucous epidermal nevus is a rare type of epidermal nevus which clinically resembles psoriatic plaques. The disease is characterized by an early onset; it appears at birth or in the first years of life. Skin lesions are accompanied with inflammation and intensive pruritus. The paper presents a case of a 51-year old man, in whom the first signs of the disease in the form of a linear erythematous, verrucous, itchy band situated on the lateral side of the right extremity appeared in adulthood. Histopathological examination showed psoriatic features. Typical anti-psoriatic treatment brought only a short period of clinical improvement